Հայասպանություն բառի պատմալեզվաբանական քննությունը - Դավիթ Գյուրջինյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье исследуются время и история создания слова հայասպանություն “арменоцид, геноцид армян”, семантическая структура слова, его терминологическая значимость, особенности употребления и лексикографическая обработка. In this article the time and the history of the formation of the word հայասպանություն “Armenocide, genocide of Armenians” are being examined, as well as the semantic structure of the word, its morphological value, peculiarities of usage and description in dictionaries.
Keywords: Language and Literature